2015
DOI: 10.1021/acs.chemmater.5b03228
|View full text |Cite
|
Sign up to set email alerts
|

Design of Self-Oscillating Polymer Brushes and Control of the Dynamic Behaviors

Abstract: A polymer brush surface with autonomous function has been designed by using a self-oscillating polymer that we developed. The self-oscillation is induced by chemomechanical energy conversion from an oscillating chemical reaction (the Belousov−Zhabotinsky (BZ) reaction) to conformational changes of polymer chains. In this study, the surface nanostructure of polymer brushes were regulated and the spatiotemporal behaviors of self-oscillation were investigated. The target polymer brush surfaces were prepared throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 38 publications
(52 reference statements)
5
52
0
Order By: Relevance
“…This peak was derived from the amide I stretching vibration of the modified polymer chains. [20] The elemental composition analyses conducted by XPS also revealed the same tendency ( Figure S2, Supporting Information). By comparing the small-range scans for C(1s) and N(1s) from the two substrates, it was found that the compositions on the photoresist-coated substrate were larger than those of the photoresist-uncoated substrate for both elements.…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations
“…This peak was derived from the amide I stretching vibration of the modified polymer chains. [20] The elemental composition analyses conducted by XPS also revealed the same tendency ( Figure S2, Supporting Information). By comparing the small-range scans for C(1s) and N(1s) from the two substrates, it was found that the compositions on the photoresist-coated substrate were larger than those of the photoresist-uncoated substrate for both elements.…”
Section: Introductionsupporting
confidence: 59%
“…[9,10] (2 of 8) 1700041 www.small-journal.com for mass transport or fluid control. [20] However, because the BZ substrates were homogeneously distributed in the BZ medium, the propagation of the chemical waves was not in a single well-defined direction, which can be a drawback considering this phenomenon's potential applications as a mass transport system. We recently reported that incorporating a gradient structure into the self-oscillating polymer brush by the sacrificial-anode ATRP method can overcome this issue.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, to improve the self‐oscillating behaviors and obtain more stable oscillations, we have investigated the relationship between surface nano‐structures and the resulting oscillating behavior . Self‐oscillating polymer brushes with different architectures were prepared by changing synthesis conditions, and surface characterization was conducted by XPS and AFM measurement (Figure a).…”
Section: Self‐oscillating Polymer Brushesmentioning
confidence: 99%